Molecular detection and characterization of human gyroviruses identified in the ferret fecal virome - Fehér, Enikő; Pazár, Péter; Kovács, Eszter; Farkas, Szilvia L; Lengyel, György; Jakab, Ferenc; Martella, Vito; Bányai, Krisztián (Archives of virology, 2014)
The recently described novel gyroviruses may infect chickens and/or humans; however, their pathogenic potential is unknown. In our metagenomic investigation, we detected many of the novel gyroviruses in the fecal viromes of ferrets with lymph node and organ enlargement. The complete genomic sequences of selected gyrovirus strains showed 90.7-99.4 % similarity to homologous reference gyrovirus strains. This study did not demonstrate an association between gyrovirus shedding from ferrets and the observed background disease; however, it provides evidence for genetic diversity among gyroviruses and raises the possibility that pet ferrets may transmit gyroviruses to heterologous hosts, e.g., humans.